2021
DOI: 10.3390/toxics9050102
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Safety Evaluations of Zingiber ottensii Valeton Essential Oil in Zebrafish Embryos and Rats

Abstract: Zingiber ottensii Valeton (ZO) exhibits pharmacological activity and has long been used in traditional medicine. However, reports about its safety profiles are limited. The present study aimed to evaluate the phytochemical profile and the toxic effects of ZO essential oil on the development of zebrafish and acute oral toxicity in rats. The essential oil was isolated from ZO rhizomes, and phytochemicals were analyzed using a gas chromatography–mass spectrometer (GC–MS). The embryotoxic and teratogenic effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 33 publications
(40 reference statements)
0
18
0
Order By: Relevance
“…These anti-inflammatory effects of ZO essential oil were examined in macrophage cell line [27]. The hydrodistilled essential oil from the rhizome of ZO was explored to contain several different constituents, with zerumbone (24.73%) identified to be the major component that had high toxicity [14]. Furthermore, it was shown that the pupae of Aedes aegypti and Culex quinquefasciatus mosquitoes were susceptible to ZO essential oil [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These anti-inflammatory effects of ZO essential oil were examined in macrophage cell line [27]. The hydrodistilled essential oil from the rhizome of ZO was explored to contain several different constituents, with zerumbone (24.73%) identified to be the major component that had high toxicity [14]. Furthermore, it was shown that the pupae of Aedes aegypti and Culex quinquefasciatus mosquitoes were susceptible to ZO essential oil [28].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported that ZO essential oil isolated from Zingiber ottensii Valeton contains several different potential compositions (assayed by the GC–MS method), including zerumbone (24%), terpinen-4-ol (18%), sabinene (15%), and β-pinene (7%) [ 14 ]. In particular, zerumbone is an interesting natural crystalline cyclic sesquiterpene because it has been stated to have application potential in chemoprevention and chemotherapy approaches, both in vitro and in vivo [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the rhizome part of Zingiber ottensii (Z. ottensii) is also empirically used to treat wound healing, relieve gastrointestinal disease, and constipation (Thitinarongwate et al, 2021). Furthermore, Zingiber officinale (Z. officinale), the most known Zingiber species, is medically used to treat respiratory infections and stomach disorders in Saudi Arabia and the rhizome, processed as a beverage combined with Arabic ginger called qahwa.…”
Section: Overview Of Empirical Usesmentioning
confidence: 99%
“…Chang et al (2012) reported that Z. zerumbet contains alkaloids, saponins, flavonoids, tannins, terpenoids, phenols, and polyphenols. Zerumbone, the most abundant compound in Z. zerumbet, is classified as monocyclic sesquiterpene and found in other Zingiber species, including Z. ottensii and Z. roseum (Al-Amin et al, 2019;Chien et al, 2016;Thitinarongwate et al, 2021).…”
Section: Bioactive Compoundsmentioning
confidence: 99%